A poética artesanal em Feito à Mão, de Lygia Bojunga - Rocha, Ludymilla Fogassi de Oliveira (2018)
The present research aims to analyze the book Feito à mão, by Lygia Bojunga, from a book-object perspective and from the creative process used in its production. According to this purpose, we try to think of the concept of handmade, based on the approaches of Sennett (2009), Martins (1973), Creni (2013) and other theorists, in order to trace a handmade poetry in the work of the writer, as pointed out by Feito à mão. In addition, we also observed the fundamental role of the hand in the “handicrafts”, as well as the joining of these with the attentive look of the craftsman, at the moment of making, and finally to reflect on the gesture of writing, which, according to Barthes (2004), “involves a return to the hand”, with the intention of enabling communication through language, and in this case a craft communication.